The using of marketing mix to improve the marketing activity о the enterprise - Riabtseva, Sofia (My University, 2014)
With the development of market relations, the establishment and functioning of the economy, which is based on the principles of marketing, much attention should be given to «Rosynka» for forming integrated and scientifically based system of organization, its development and management current conditions.
Keywords: marketing; market relations; маркетинг; ринкові відносини; рыночные отношения